A one-dimensional soft and color-programmable light-emitting device. Issue 6 (5th January 2018) - Zhang, Zhitao; Shi, Xiang; Lou, Huiqing; Cheng, Xunliang; Xu, Yifan; Zhang, Jing; Li, Yiming; Wang, Lie; Peng, Huisheng
Abstract : A one-dimensional soft and color-programmable light-emitting device is developed with high stretchability. Abstract : A one-dimensional soft and color-programmable light-emitting device is developed by sandwiching an elastic light-emitting tube with two aligned carbon nanotube sheets. It can be stretched by over 200% without obvious fatigue in its illuminant property. Furthermore, its emission light can be controlled for different colors with tunable intensities that are independent of the observation angles. Based on its unique one-dimensional architecture, it can be continuously produced and assembled into various patterns or fabrics for large-scale application.